패션에서의 패러디 변화양상에 관한 연구 - 정정희; Jung-hee Jung (Fashion & textile research journal, 2024)
This study examines the creation method using parody in fashion, which has changed from the first half of the 20th century to the present day, by considering the creation method expressed in art. A literature review and case studies were conducted for this research method. The scope of this case study was to examine designer works that attempted an artistic approach, focusing on contemporary fashion in the 20th century to the present. First, it was found that parody, as a creative method in fashion, creates works that reflect designers' new perspectives or perspectives in the form of variations that vary from time to time. Second, the forms of variation that vary from time to time demonstrate Poire's imitation technique in the modernist era. Imitation and critical parody techniques were used in the postmodern era. In the post-contemporary era, the extended parody-type appropriation and re-transmission techniques were used. Third, when comparing creation techniques using parody in art and fashion by period, it was found that the fashion technique, which followed the creation technique in art, adopted the same method as the art technique, as it approached recently.